Prevalence of Behavioral and Emotional Problems among Omani Children as Predicted by Some Demographic Variables - Tagharid T. Al Said; Ian S. Hamilton; Nicola Birdsey (Sultan Qaboos University, 2014)
This study aimed to identify the prevalence of behavioral and emotional problems in children in Oman and demographic variables correlated with these. A random sample of 200 pupils from grades 1-4 in the Governorate of Muscat was selected using the OMBEP measure (Al Said, Birdsey, & Stuart-Hamilton, 2012). Multiple linear regression analysis showed three variables are able to predict emotional and behavioural problems including: the educational level of the father (only when it is below bachelor's degree), the number of hours spent watching T.V., and grade 3 (children in grade 3 are more likely to experience the negative effects of emotional and behavioural problems as compared with children in other grades). However, there are variables that have a positive role in reduction of behavioural and emotional problems. These are: the mother's educational level when it is a bachelor's degree, the existence of a nursemaid, and the effect of having first grade education.